2020
DOI: 10.48550/arxiv.2009.08193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do Scaling Agile Frameworks Address Global Software Development Risks? An Empirical Study

Abstract: Driven by the need to coordinate activities of multiple agile development teams cooperating to produce a large software product, software-intensive organizations are turning to scaling agile software development frameworks. Despite the growing adoption of various scaling agile frameworks, there is little empirical evidence of how effective their practices are in mitigating risk, especially in global software development (GSD), where project failure is a known problem.In this study, we develop a GSD Risk Catalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(129 reference statements)
0
0
0
Order By: Relevance
“…Despite the introduction of recent Agile practices, such as SAFe [28] and Disciplined Agile Delivery (DAD) [29], Scrum introduced in 1993 [30], continues to maintain its dominant presence in Agile practices, spanning across software development, including BI implementation. This consistency showed that BI implementation followed the broader software development trend.…”
Section: B Scrum: the Most Widely Used Agile Practice In Bi Implement...mentioning
confidence: 99%
“…Despite the introduction of recent Agile practices, such as SAFe [28] and Disciplined Agile Delivery (DAD) [29], Scrum introduced in 1993 [30], continues to maintain its dominant presence in Agile practices, spanning across software development, including BI implementation. This consistency showed that BI implementation followed the broader software development trend.…”
Section: B Scrum: the Most Widely Used Agile Practice In Bi Implement...mentioning
confidence: 99%